Intertemporal efficiency and equity under hyperbolic preferences: Ex ante versus ex post procrastination - Ralph Winkler (University of Heidelberg, Department of Economics, 2004)
In this paper I extend the well known result that a hyperbolically discounting agent postpones costs into the future. If society has hyperbolic inter-temporal preferences, it may be optimal from an ex ante point of view to postpone structural change from a polluting to a non polluting production sector into the future (ex ante procrastination). The consequences of ex ante procrastination are discussed for three different behavioral patterns. I show that, depending on the assumed behavioral regime, ex ante procrastination may lead to ex post procrastination, i.e. de facto no investment in the non polluting sector is undertaken over the whole time horizon, although investment was optimal from an ex ante point of view. Furthermore, the ex post implemented investment plan may be inefficient if it is not dictatorial. Hence, in the case of hyperbolic preferences there is a potential trade-off between inter-temporal efficiency and equity.
Keywords: D91; Q25; C61; 330; dynamic optimization; emission abatement; hyperbolic preferences; intergenerational equity; inter temporal decision theory; procrastination; Umweltschutzinvestition; Intertemporale Entscheidung; Intertemporale Allokation; Theorie